Modification of Conveyor with Monitoring of Running Hours, Current, and Voltage Based on Arduino Mega 2560 Microcontroller “Model G.A.S” at Iskandar Pangkalan Bun Airport - Asrif Arestya; Kurniaty Atmia; Djunaedi (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STAI Raudhatul Akmal, 2025)
Conveyor belts are vital facilities in airport operations, but their maintenance systems are often reactive, inefficient, and high-risk. This study aims to design and build a monitoring system for conveyor modifications at Iskandar Pangkalan Bun Airport that can monitor running hours, current, and voltage in real time to support condition-based maintenance. The method used is applied Research and Development (R&D) by building a prototype based on the Arduino Mega 2560 microcontroller. This system integrates an ACS712 current sensor, a ZMPT101B voltage sensor, a DS3231 Real Time Clock (RTC) module, a TFT Display, and an SD Card module for data logging. Test results indicate that the system operates effectively with stable and accurate sensor readings. The measured current remains consistent at 1.56 A under normal load conditions, voltage fluctuates within a reasonable range (214.74 V to 222.23 V), and the RTC module demonstrates high accuracy with a time deviation of only 1-2 seconds over 24 hours. The system successfully stored historical data on the SD Card, including date, time, running hours, voltage, and current. Thus, this monitoring system has proven reliable in providing accurate data essential for improving maintenance efficiency and operational reliability of the conveyor.